Stretchable, mechanically resilient, and high electromagnetic shielding polymer/MXene nanocomposites. Issue 22 (28th January 2021) - Aakyiir, Mathias; Kingu, Mary‐Ann Stephen; Araby, Sherif; Meng, Qingshi; Shao, Junyan; Amer, Yousef; Ma, Jun
Abstract: The increasingly disturbing electromagnetic wave pollution has intensified research for high‐performance shielding materials to protect humans and the environment. It remains a great challenge to combine high electromagnetic interference (EMI) shielding performance with mechanical robustness and stretchability. These crucial features have been simultaneously achieved in this work by using a facile method to prepare elastomer/MXene nanocomposites. An EMI shielding effectiveness of 49 dB was obtained from a 1‐mm thick nanocomposite film at 19.6 vol% of MXene; the film has a density of 1.25 g/cm 3 . The outstanding electrical conductivity of MXene – 4350 ± 125 S·cm −1 – provided free charge carriers in the matrix to absorb electromagnetic signals, leading to the dominance of absorption mechanism over reflection mechanism. Owing to a nanofiller modification step, the nanocomposite films demonstrated not only outstanding EMI shielding but sufficient strength and stretchability. A nanocomposite at 14.0 vol% exhibited Young's modulus of 15.85 ± 0.75 MPa and tensile strength 25.94 ± 0.81 MPa with elongation at break of 170 ± 5.6%, which relates to high stretchability. These impressive properties make our nanocomposites suitable for use in harsh environments as well as applications in stretchable devices, protective clothing, aerospace, aircraft, and automotive industries. Abstract : Mathias Aakyiir, Jun Ma and colleagues report high electromagnetic shielding performance by using 1‐mm thick elastomeric nanocomposites containing novel 2D nanofiller, Ti3 C2 Tx MXene, with a density of 1.25 g/cm 3 . The nanocomposites synthesised via a latex compounding method exhibit sufficient mechanical resilience, making them suitable for applications in stretchable devices, protective clothing, aerospace, aircraft and automotive industries.